The Effect of Education Level on Accepting The Reuse of Treated Effluent in Irrigation - Al-Najar, Husam; Hamarneh, Basel El (Universitas Pendidikan Indonesia, 2019)
Gaza strip suffers from a serious shortage in water resources due to the continuous increase in population, life changes, political conditions and drought caused by climate change. Due to increased demand for water for domestic use, resulting accumulation of large quantities of wastewater in the treatment plant in Rafah. Therefore, reuse of treated wastewater is one of the most recently accepted approaches to save groundwater or domestic use. The aim of this research is to study the treated effluent quality from Rafah Treatment Plant, in addition to the effect of education level of the farmers on reusing treated wastewater for irrigation. A questionnaire was distributed to farmers to investigate the acceptance of using treated effluent for irrigation, meanwhile the effluent parameters tested were BOD, COD, TKN, NH4, NO3, P, Cd, Pb, and Cu accounted for 110, 250, 108, 127, 0.23, 17.9 mg/l, 0.003, 0.001, and 19.9 Âµg/l. Most of reuse parameters were higher than the recommended levels for the effluent reuse based on the recommended Palestinian Standards for irrigation. About 80.7% of farmers accept using treated wastewater in irrigation and the Chi-square test analysis showed that, at P-value =0.00095 Î±= 0.05, there is a close relationship between the educational level of farmers and the acceptance of using of treated wastewater in irrigation, as long as it is safe and healthy.Â